2001
DOI: 10.1085/jgp.118.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Altered State Dependence of C-Type Inactivation in the Long and Short Forms of Human Kv1.5

Abstract: Evidence from both human and murine cardiomyocytes suggests that truncated isoforms of Kv1.5 can be expressed in vivo. Using whole-cell patch-clamp recordings, we have characterized the activation and inactivation properties of Kv1.5ΔN209, a naturally occurring short form of human Kv1.5 that lacks roughly 75% of the T1 domain. When expressed in HEK 293 cells, this truncated channel exhibited a V1/2 of −19.5 ± 0.9 mV for activation and −35.7 ± 0.7 mV for inactivation, compared with a V1/2 of −11.2 ± 0.3 mV for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 54 publications
(91 reference statements)
6
44
0
Order By: Relevance
“…1D), and a half-inactivation potential of Ϫ21.0 Ϯ 1.2 mV (Fig. 1E), which was consistent with previous studies from our laboratory and others (8,32). In the current study, we were particularly interested in the shape of the inactivation-voltage relationship, with FL Kv1.5 exhibiting a flat voltage dependence of inactivation at positive potentials (Fig.…”
Section: C-and U-type Inactivation In Kv1supporting
confidence: 92%
See 2 more Smart Citations
“…1D), and a half-inactivation potential of Ϫ21.0 Ϯ 1.2 mV (Fig. 1E), which was consistent with previous studies from our laboratory and others (8,32). In the current study, we were particularly interested in the shape of the inactivation-voltage relationship, with FL Kv1.5 exhibiting a flat voltage dependence of inactivation at positive potentials (Fig.…”
Section: C-and U-type Inactivation In Kv1supporting
confidence: 92%
“…Minor et al (31) hypothesized that point mutations within the T1 domain of Kv1.2 influence activation gating by altering the stability of channel closed states. Interestingly, kinetic modeling of inactivation in Shaker, Kv2.1, Kv3.1, and Kv1.5⌬N209 suggest that the apparent U-type voltage dependence of inactivation arises from accelerated inactivation from closed states of the channel (4,5,8). In our experiments, we observed that all of the T1 deletions (Kv1.5⌬N188, Kv1.5⌬N209, and Kv1.5T19ϩ163) and point mutations (Kv1.5AAQL) which impart U-type inactivation features to Kv1.5 also result in significant hyperpolarizing shifts of channel activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcripts for these channels are detected in pyramidal neurons (Pan et al, 2004) and the NAc is labeled with a Kv1.5-specific antibody (Chung et al, 2000). However, homomeric Kv1.5 channels form functional, delayed rectifier K ϩ channels presenting a slowinactivating rate with poor cumulative properties (Coetzee et al, 1999;Kurata et al, 2001;Song, 2002). In a heterologous system, heteromeric assembly of Kv1.5 and Kv1.4 ␣ subunits forms functional channels expressing A-type-like inactivation and recovery from inactivation properties.…”
Section: Discussionmentioning
confidence: 99%
“…In some Kv isoforms (Kv1.4, Kv3.1, and Kv4.2), a fast inactivation takes place in which the cytoplasmic N-terminus acts as a ''ball-and-chain'', occluding the internal cavity of the opened Kv channel [5]. Almost all Kv channels display a slow type (also termed C-type) inactivation which often span seconds [6,7]. This C-type inactivation appears to involve destabilization of the outer channel pore surrounding the selectivity filter [8].…”
Section: Introductionmentioning
confidence: 99%